Provide a Model for Establishing a Comprehensive Knowledge Management System in Knowledge-Based Organizations Based on Success Factors - Saeed Ghorbani; Shayan Naghdi Khanachah (goodwood publishing, 2020)
Purpose: This study provides a model for establishing a comprehensive knowledge management system in knowledge-based organizations based on success factors. Research Methodology: A researcher-made questionnaire was used to examine these factors and to present the model. The statistical population of this study comprised all managers and employees of knowledge-based organizations. There were 150 individuals in total, and 108 were randomly selected as the research sample. Results: The results of factor analysis showed that all seven factors under study explain 65.16% of the total variance, which is acceptable. The results of the Friedman test also showed the first to the seventh priorities of the effective factors of knowledge success in construction projects, including human resource development, knowledge-based orientation, knowledge evaluation and transfer, information systems infrastructure, business culture, and modeling. Finally, there was a conflict between people. A model was designed according to the aforementioned priorities. Conclusions: This study developed a model for knowledge management in knowledge-based organizations, highlighting key factors, such as human resource development and knowledge transfer. The model directs tacit knowledge towards organizational growth. Future research could extend its applicability to other types of organizations. Contributions: This study provides a mechanism for establishing and implementing a comprehensive knowledge management system in knowledge-based organizations. By leveraging expert knowledge and focusing on tacit knowledge, organizations can enhance value creation and process efficiency.